Government Communication Strategies in Combating Online Gambling in Indonesia - Virna Estriana; Annisa Ratu (Pusat Publikasi Nusantara, 2024)
Online gambling has become one of the biggest challenges faced by the Indonesian government in recent decades. This study uses a qualitative approach with a case study design to analyze the government's communication strategy in combating online gambling in Indonesia. Data were collected through in-depth interviews with online gambling victims, conducted directly and via the Zoom and Google Meet platforms. Thematic analysis techniques were used to analyze data. The results show that the communication strategies of the government in tackling online gambling have not been fully effective, mainly due to limitations in message delivery, use of communication channels, and enforcement of regulations. It is hoped that through this collaborative approach, the prevalence of online gambling can be significantly reduced, and the community can be better protected from its negative impacts. This research is expected to serve as a reference for future studies in the fields of communication, law, and public policy related to online gambling.